(3QSGdI GdQhV GdfVQ aj GdcdGe Ydi GdNVQs - (3eQYj Hf jhSa Hf CHj HcQ Hf CMeO GdcQej GdebOSj GdMfHdi,J (B1033 (3g` s
(3ChdgG (B:s
(3GdMeO ddg LGYd GdYdeGA GdGYdGe hQKI GdGfHjGA Ydjge GdSdGe hHYO agPg cdeGJ jSjQI ai YHGOGJ eSJfjQI JJYdb HTCf GdNVQ Ydjg GdSdGe s
(3BNQgG (B:s
(3MJi jKHJ HGdOdjd GdUMjM hLhOg hGdOdjd efJa aGfJaJ MjGJg Edi GdGf aJCed hGddg JYGdi CYde Je HMeO Gddg JYGdi s
(3Vef eLehY , JQJjHgG (B: (3GdcJGH (B2s
(3GdfSNI HgG MhGTs
(3HgG fXGe GdJYbjHIs
(3fbdJ Yf NW ef NW eDdags
(3bQf GdfSN (B:s
(3GdbQf GdMGOj YTQs
(3eUOQ GbJfGA GdCUd (B:s
Keywords: (3GdJUha hGdBOGH GdTQYjIs